LEGAL PROTECTION OF DATABASES - Gupta, V.K.; Pangannaya, N.B. (Malaysian Journal of Library and Information Science, 2000)
The computer-based databases have made significant value addition in information products and services, and have enabled fast access to information. The growing role of databases for information access has brought to the fore questions of legal rights of the owners and users of the databases. The paper examines current developments in the legal protection of databases. The developments in the European Union (EU) and USA show significant departure from the existing practices in many countries. The salient aspects of these developments, the relevant provisions of the international agreements, the proposed WIPO draft database treaty, the legal implications of the protection of databases within the context of promotion and progress of science, and the role of the library and information science profession, are also discussed.